Efficiency in the olympic games: The role of mobility and inequality - Csurilla, G.; Ferto, I.; Baráth, L. (Journal of Sports Economics, 2026)
This paper presents the analysis of Olympic efficiency by introducing a weighted performance score that values both medals and near-podium finishes and by applying a random-parameters stochastic frontier model with heteroscedastic inefficiency to the Summer Games, 1996-2020. Unlike earlier studies, we allow production elasticities to vary across countries and examine the role of sports diversification in shaping efficiency. The results highlight the importance of broad participation across disciplines, showing that diversification not only raises potential output but also reduces inefficiency. Distributional analysis further reveals modest declines in inequality and meaningful opportunities for upward mobility, even as top performers persist. The findings suggest that efficient Olympic nations combine scale, diversification, and organizational quality, offering policy lessons beyond resource levels alone.